PENGARUH MOTIVASI KERJA, KERJASAMA TIM DAN KOMITMEN TERHADAP KINERJA KARYAWAN HONORER PADA PUSKESMAS SIGAMBAL - Resita Aulia Kania; Yuniman Zebua; Yanto Zelibu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of work motivation, teamwork, and organizational commitment on employee performance. This research uses a quantitative approach with an explanatory research design. The population consists of employees, with a total sample of 99 respondents selected using a specific sampling technique. Data were collected through questionnaires using a Likert scale. The data analysis techniques include validity testing, reliability testing, classical assumption tests, and multiple linear regression analysis. The results show that partially, work motivation has a positive and significant effect on employee performance with a t-value of 3.245 and a significance value of 0.002. Teamwork also has a positive and significant effect with a t-value of 4.276 and a significance value of 0.000. Furthermore, organizational commitment has a positive and significant effect with a t-value of 3.327 and a significance value of 0.001. Simultaneously, work motivation, teamwork, and organizational commitment significantly affect employee performance with an F-value of 42.318 and a significance value of 0.000. The coefficient of determination (R²) of 0.716 indicates that 71.6% of employee performance can be explained by these variables, while the remaining is influenced by other factors outside this study. This study implies that improving work motivation, strengthening teamwork, and enhancing organizational commitment are essential factors in improving employee performance